Early EEG correlates of word frequency and contextual predictability in reading. Issue 5 (2nd June 2020) - Sereno, Sara C.; Hand, Christopher J.; Shahid, Aisha; Mackenzie, Ian G.; Leuthold, Hartmut
ABSTRACT: Previous research into written language comprehension has been equivocal as to whether word frequency and contextual predictability effects share an early time course of processing. Target word frequency (low, high) and its predictability from prior context (low, high) were manipulated across two-sentence passages. Context sentences were presented in full, followed by word-by-word presentation (300 ms SOA) of target sentences. ERPs were analysed across left-to-right and anterior-to-posterior regions of interest within intervals from 50 to 550 ms post-stimulus. The onset of significant predictability effects (50–80 ms) preceded that of frequency (P1, 80–120 ms), while both main effects were generally sustained through the N400 (350–550 ms). Critically, the frequency-predictability interaction became significant in the P1 and was sustained through the N400, although the specific configuration of effects differed across components. The pattern of findings supports an early, chronometric locus of contextual predictability in recognising words during reading.